Mitochondrial ROS potentiates indirect activation of the AIM2 inflammasome - Crane, Deborah D. (Frontiers Media S.A., 2014)
Activation of the inflammasome is important for the detection and clearance of cytosolic pathogens. In contrast to avirulent Francisella novicida (Fn), infection with virulent Francisella tularensis ssp tularensis does not trigger activation of the host AIM2 inflammasome. Here we show that differential activation of AIM2 following Francisella infection is due to sensitivity of each isolate to reactive oxygen species (ROS). ROS present at the outset of Fn infection contributes to activation of the AIM2 inflammasome, independent of NLRP3 and NADPH oxidase. Rather, mitochondrial ROS (mROS) is critical for Fn stimulation of the inflammasome. This study represents the first demonstration of the importance of mROS in the activation of the AIM2 inflammasome by bacteria. Our results also demonstrate that bacterial resistance to mROS is a mechanism of virulence for early evasion of detection by the host.